The equation is

$$y'' - xy' + y = 0$$

So far I have the recurrence relation -

$$a_{n+2} = \dfrac{(n-1)a_n}{(n+1)(n+2)} $$

From this -

$a_2 = \dfrac{-a_0}{2!}$

$a_3 = 0$

$a_4 = \dfrac{-a_0}{4!}$

$a_5 = 0$

$a_6 = \dfrac{-3a_0}{6!}$

and so on..

The question asks for the first five non-zero terms of a general series solution of the d.e, seperating out for $a_0$ and $a_1$

How do I compute this?


  • $\begingroup$ If you've come this far, I think you already have the solution. It is $y = a_0\left(1 - \frac{1}{2!}x^2 - \frac{1}{4!}x^4 - \frac{3}{6!}x^6 - \ldots\right) + a_1x$. (I'm trusting your calculation.) $\endgroup$ – Tunococ Apr 27 '14 at 21:53
  • $\begingroup$ Where did the first 1 come from and also, where did the last $a_1x$ come from? $\endgroup$ – Finance Apr 27 '14 at 21:55
  • $\begingroup$ When you try to solve an ODE with the power series method, you start with assuming $y = a_0 + a_1x + a_2x^2 + \ldots$. That is how you eventually get the recurrence and solve for $a_n$. Once you know all the $a_n$, you should put them back into the assumed form of the solution that you started with. $\endgroup$ – Tunococ Apr 27 '14 at 21:57
  • $\begingroup$ Ok, but I still can't see where the first $a_0$ comes from, or the last $a_1$x? I didn't compute these? $\endgroup$ – Finance Apr 27 '14 at 22:01
  • $\begingroup$ These are supposed to be unknown. Your ODE is second-order, so the solution is not uniquely determined unless you give it two conditions. Note that this is the same situation as when you solve a second-order linear ODE with constant coefficients. $\endgroup$ – Tunococ Apr 27 '14 at 22:03

The differential equation \begin{align} y^{''} - x y^{'} + y = 0 \end{align} can be solved via a power series of the form \begin{align} y(x) = \sum_{k=0}^{\infty} a_{n} x^{n} = a_{0} + a_{1} x + a_{2} x^{2} + \cdots . \end{align} It is fairly evident that \begin{align} \sum_{k=0}^{\infty} k(k-1) a_{k} x^{k} = \sum_{k=0}^{\infty} (k-1) a_{k} x^{k} \end{align} which yields the equation for the coefficients \begin{align} a_{k+2} = \frac{ (k-1) a_{k} }{ (k+1) (k+2) }. \end{align} It is discovered that $a_{3} = 0 \cdot a_{1}$. Since, for $k$ being odd, say $k \rightarrow 2k+1$, \begin{align} a_{2k+3} = \frac{k a_{2k+1} }{(k+1)(2k+3)} \end{align} it is clear that all the odd coefficients depend of $a_{3}$ for $k \geq 1$ and leads to $a_{2k+1} = 0$ for $k \geq 1$. The even $k$ values are \begin{align} a_{2} &= - \frac{a_{0}}{2!} \\ a_{4} &= - \frac{a_{0}}{4!} \\ a_{6} &= - \frac{(1 \cdot 3) a_{0}}{6!} \\ a_{8} &= - \frac{(1\cdot 3 \cdot 5)a_{0}}{8!} \end{align} which has the general form \begin{align} a_{2k} = - \frac{a_{0}}{2^{k} k! (2k-1)}. \end{align} The series for $y(x)$ now be seen in the form \begin{align} y(x) = a_{0} + a_{1} x - a_{0} \sum_{k=1}^{\infty} \frac{ x^{2n} }{2^{k} k! (2k-1)}. \end{align}

The power series discovered can be evaluated as follows. Consider \begin{align} \partial_{x} \left( \sum_{k=1}^{\infty} \frac{ x^{2n-1} }{2^{k} k! (2k-1)} \right) &= \sum_{k=1}^{\infty} \frac{ x^{2n-2} }{2^{k} k!} = \frac{1}{x^{2}}( e^{x^{2}/2} -1). \end{align} Integrating both sides \begin{align} \sum_{k=1}^{\infty} \frac{ x^{2n} }{2^{k} k! (2k-1)} &= x \int^{x} \frac{e^{u^{2}/2} -1}{u^{2}} du = x \left[ \sqrt{\frac{\pi}{2} } erfi\left( \frac{x}{\sqrt{2}} \right) - \frac{e^{x^{2}/2}}{x} + \frac{1}{x} \right] \\ &= \sqrt{\frac{\pi}{2} } \cdot x \cdot erfi\left( \frac{x}{\sqrt{2}} \right) - e^{x^{2}/2} + 1. \end{align} With this series the general solution of $y(x)$ can be sen by \begin{align} y(x) &= a_{0} + a_{1} x - \sum_{k=1}^{\infty} \frac{ x^{2n} }{2^{k} k! (2k-1)} \\ &= a_{1} x - a_{0} \left[ \sqrt{\frac{\pi}{2} } \cdot x \cdot erfi\left( \frac{x}{\sqrt{2}} \right) - e^{x^{2}/2} \right], \end{align} where $erfi(x)$ is the imaginary error function (erfi(x) = -i erf(ix)).

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.